Lexical Representation of Ideas about Conquest of Siberia in Chronicles of 17-18 Centuries - L. A. Inyutina (Научный диалог, 2018)
The work is devoted to the actual problem of language conceptualization of Siberia space of 17th-18th centuries. The semantic field of space, reconstructed for the first time on the basis of the Esipovskaya chronicle, is considered as a model of the regional spatial picture of the world. The semantics of lexical units denoting military actions (offensive, retreat, defense, defeat and conquest of the enemy) are analyzed in cognitive aspect. The article defines the peculiarities of the lexical representation of the semantic paradigm “Way - fight,” which constructs the far periphery of the semantic sphere “Moving in space,” which along with the semantic spheres “Russ, Moscow Kingdom,” “Physical space, expanse” structures the semantic field of space in this text. It is found that the actualization of such an essential characteristic of the Siberian space as the conquest of a new territory is expressed by the semantics of a large number of lexemes linked by the relations of synonymy, antonymy, conversion, lexical-word-formation relations. It is established that such semantic and lexical-word-formation relations form semantic paradigms of the whole reconstructed field of space and are a linguistic reflection of interest in objects attracting public attention. It is proved that in the text of the Esipovskaya chronicle Siberia is such an object. The method of the field description of vocabulary allowed to specify their lexical meaning in the course of the lexical paradigm analysis and, having revealed the structure of the semantic field, to reconstruct essential parameters of the Siberian spatial picture of the world.